Web-Based Clinical Teleconsultation for Mothers and Children at RSIA Muhammadiyah, Probolinggo City - Ramadhani, Riska Isyraq; Roziqin, Mochammad Choirur; Wicaksono, Andri Permana; Yunus, Muhammad (International Journal of Healthcare and Information Technology, 2025)
Health services at RSIA Muhammadiyah Probolinggo City are currently provided face-to-face to patients who come directly to the hospital. This approach often leads to long queues in several polyclinics, resulting in discomfort and prolonged waiting times for patients. One solution to this problem is to utilize information technology through a website-based teleconsultation system for maternal and child health services. This research applied a research and development (R&D) approach using the waterfall development model. Data collection techniques included interviews, documentation review, and direct observation of existing services. The system design and development stages were carried out sequentially, covering analysis, design, implementation, testing, and deployment of the website-based teleconsultation platform. The resulting system is a web-based clinical teleconsultation application designed for maternal and child health services at RSIA Muhammadiyah Probolinggo City. The system provides features to support online consultations, including real-time chat and video consultations via Google Meet, to facilitate interaction between patients and healthcare professionals without requiring in-person visits. The development of this teleconsultation system is expected to improve the quality of online healthcare services at RSIA Muhammadiyah Probolinggo City. The use of teleconsultation can reduce patient queues, shorten waiting times, and enhance comfort for patients while also expanding access to maternal and child health services.